Context-Aware Systems and Applications 4th International Conference, ICCASA 2015, Vung Tau, Vietnam, November 26-27, 2015, Revised Selected Papers - Vinh, Phan Cong; Alagar, Vangalur (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2016)
This book constitutes the thoroughly refereed proceedings of the 4th International Conference on Context-Aware Systems and Applications, ICCASA 2015, held in Vung Tau, Vietnam, in November 2015. The 44 revised full papers presented were carefully selected and reviewed from over 100 submissions. The papers cover a wide spectrum of issues in the area of context-aware systems (CAS) and context-based recommendation systems. CAS is characterized by its self- facets such as self-organization, self-configuration, self-healing, self-optimization, self-protection and so on whose context awareness used to dynamically control computing and networking functions. The overall goal of CAS is to realize nature-inspired autonomic systems that can manage themselves without direct human interventions.